Transforming Education and Learning through Chat GPT: A Systematic Literature Review - Arie Wahyu Prananta; Ruth Rize Paas Megahati S; Nugroho Susanto; Jean Henry Raule (Postgraduate, University of Mataram, 2023)
Technology is generally interpreted as anything that can provide us with convenience in many ways. Technology also has a huge impact on education and learning. These two things become increasingly inseparable because their roles are interconnected. One of them is by using Chat GPT. The purpose of this research is to explain Transforming Education and Learning through Chat GPT. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses. We must know and practice changes in education and learning patterns at all levels of education by describing the characteristics of learning that are currently needed. by using GPT Chat digital technology which has benefits and reasons for using this technology, such as using GPT chat in the transformation of education and learning. GPT chat has many benefits in education and learning but GPT chat is only a tool and the results depend on the data available during training and the model's understanding of the question and context. Although Chat GPT has its benefits, be wise in using the information provided and don't hesitate to verify important information from trusted sources. GPT chat is important because it provides benefits in various fields, such as customer service, education, research, product development, language skills development, and advancing human-machine interface technology